Apropriação e ressignificação de espaços livres públicos ociosos no Conjunto Jardim Maguari, em Belém, Pará - Araújo, Kayan Freitas de (2023)
Urban planning processes in cities are largely part of a system centered on bureaucratic and authoritarian means known as Top-Down, in which the transdisciplinary aspect inherent to these processes dissolves, in order to limit decision-making to specific groups of society, reducing popular participation in city planning. In this context, it may happen that the “imposed” city does not correspond to the demands of contemporary society or generate problems that can be even more reverberated, in some cases, due to the inefficiency of public management in urban management. In this scenario, collaborative actions are identified as an insurgency against urban issues, whose objective is the recovery of open public spaces in the city to enable appropriation by the community. However, the redefinition of the place goes hand in hand with the transformations in the landscape that affect both the changes in the physical space and the social dynamics and interactions with the built environment. The decentralization and democratization of power in decision-making associate collaborative urban interventions with the Bottom-Up model, since the results start from interactions between different social groups, in order to generate results closer to the real demands of society. In the practice of urbanism, the Jardim Maguari housing complex (Belém/PA) constitutes a case study for this research because it fits in this context. In this sense, previously idle public spaces of the Jardim Maguari housing complex intervened through collaborative actions, two associated with the Bottom Up type (Espaço Criança Feliz and Pracinha da Alameda 20C) and a Top-Down (Odézio Mozart square) are analyzed. From which are investigated the contributions of the Bottom-Up processes for the appropriation and resignification of idle public spaces in the housing complex. Bibliographical research, documentary research, semistructured interviews, direct observation and behavioral mapping are used as research methods to contextualize the case study, describe urban intervention processes and analyze the use and interactions with the built environment after urban interventions. From this, the research shows the importance of popular participation for the efficiency of the public space, as it allows the population to take ownership of the urban intervention process and contribute substantially to the development of the proposal, providing increasingly better results.